Problem structuring illegal logging policies in West Aceh - Safrida, Safrida; Maulida, Desi; Latif, Ikhwan Rahmatika; Safrida, Nila (Universitas Merdeka Malang, 2023)
The rise of illegal logging practices requires the government to be more serious in tackling this problem with policies as an effort to control illegal logging without permits. This study aims to analyze the effectiveness of the implementation of illegal logging policies in West Aceh District using the structuring problem approach and to find out the causes and efforts made. The method used is a case study approach, data collection techniques using triangulation. The results of the study traced if the main causes of illegal logging in terms of structuring the problem of inappropriate program policies designed by the government included supervision, socialization, and policies for providing assistance to community. Judging from the ROCCIPI theory, indicates that forest utilization policies have not been focused on the economic conditions of th ecommunity so that it opens up gaps for individuals who carry out illegal logging, lack of solid communication between stakeholders, and capacity problems (lack of organizing resources). Therefore, it is necessary to provide alternative regulatory solutions that take into account the community’s economic ,streng then communication between stakeholders, and approach the community so that they do not carry out forest destruction followed by the right alternative solutions offered to the community.